KEBIJAKAN PAKISTAN TERHADAP TEHREEK-I-TALIBAN PAKISTAN SETELAH KEMENANGAN TALIBAN DI AFGHANISTAN (2021-2022) - Agnes Putri Eka Nurzaman; Prihandono Wibowo (Journal Publicuho, 2024)
This research aims to determine Pakistan's policy towards the Pakistan Tehreek-I-Taliban after the Taliban's victory in Afghanistan (2021-2022). The type of research used is explanatory using qualitative methods. This research uses the concept of terrorism and counterterrorism theory. According to Schmid in the Handbook of Terrorism Research in 2011. In response to the increasing number of TTP terror figures in Pakistan after the Taliban's victory over Afghanistan in 2021-2022, the Pakistani government implemented two counterterrorism policies which were divided into two approaches, namely the soft approach and the soft approach. rough approach (hard approach). The approach to counterterrorism policy can be relative, meaning that the implementation of the policy may differ from one country to another, depending on the conditions faced by that country. The research results show that Pakistan has two methods in implementing policies: a soft approach and a hard approach. Pakistan implemented a soft approach policy by mediating with the TTP and choosing the Afghan Taliban as a mediator. Meanwhile, Pakistan implemented a tough approach policy by launching cross-border air strikes into Afghanistan targeting TTP members.